Les ergonomes peuvent-ils rester borgnes ? À propos de la relation intervention-formation-genre - Marianne Lacomblez; Edmée Ollagnier; Catherine Teiger (Perspectives Interdisciplinaires sur le Travail et la Santé)
There is little room for the combining of intervention, training and gender in ergonomics and the prevention field. Nonetheless, not taking gender into account in a project’s conception narrows its impact. The persistent inequality between women and men in the work field is still worthy of mention as are the differences in their work activity and environment for the same job. There are many stereotypes underlying these disparities, and the world of prevention, training, and ergonomics has great difficulty in putting them aside. Determining the male and female workers’ place in the production process constitutes an essential element of prevention actions. However, work health professionals do not yet have a very good grasp of the issue. Training thus becomes a crucial resource where trainers and trainees can work together on the knowledge and representations drawn from their own experiences; gender research can help to improve this scenario.